Protective role of heat shock transcription factor 1 in heart failure: A diagnostic approach. Issue 6 (30th October 2018) - Haybar, Habib; Shahrabi, Saeid; Rezaeeyan, Hadi; Shirzad, Reza; Saki, Najmaldin
Abstract: Objective: Nonexpression or expression inhibition of protective factors has been determined in the occurrence of heart failure (HF). Heat shock transcription factor 1 (HSF1) is among such factors, which reduces the incidence of HF by controlling cardiac hypertrophy and fibrosis. In this study, molecular mechanisms for nonexpression of HSF1 in HF patients have been investigated. Materials and methods: This review paper is based on the material obtained via PubMed search of 1996–2018. The key search terms were "heart failure, " "heat shock transcription factor 1, " "hypertrophy", "fibrosis, " and "apoptosis." Results: Although factors such as janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) and heat shock proteins (HSPs) may respectively increase and decrease susceptibility to HF, in some circumstances, these factors may unexpectedly prevent HF progression. Conclusion: Finally, identification of molecular pathways expressed by various factors could be used to design appropriate treatments or to employ strategies inducing the expression of HSF1 to prevent HF. Abstract : This paper is about the protective role of heat shock transcription factor 1 (HSF1) in heart failure. It also discusses about the therapeutic approach of HSF1 in heart failure.